Mental Health: A Study of Al-Kindi’s Philosophical Thoughts of The Soul - Puspita, Rana Indah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2023)
Mental health for every individual, starting from the family, school, workplace, to the general public has become the main focus at this time. In 2020, when the massive spread of the COVID-19 virus, many people's mental health was disturbed. In the current condition of society, it appears that the mental health of each individual cannot be generalized. Good health enables people to realize their potential, cope with the normal stresses of life, work productively and contribute to their communities. Al-Kindi is a philosopher who is very tenacious in carrying out his shari'at. One of the philosophies studied by Al-Kindi is the philosophy of the soul. The purpose of this study is to find out preventive measures that can be taken to avoid mental illness. This research uses a type of qualitative research, based on library research (literary study). The research approach used in this article is a historical approach and a philosophical approach. This study uses a rationalistic approach with comparative analysis techniques, namely comparing one reference with another. The conclusion of this research is when you want a calm soul, you have to use rational (reason). Because desire and love are sensuous will experience destruction and annihilation. Meanwhile, rational love is always eternal and constant and does not experience destruction and loss. That's why, people who want to be happy and prevent themselves from being disturbed by sadness, then he must make his love and desire in the rational world not in the sensory world.